IMPLEMENTASI NILAI-NILAI RELIGIUS BERBASIS MODERASIS BERAGAMA TERHADAP PENDIDIKAN PONDOK PESANTREN (Study Kasus Di Pondok Pesantren Nurul Wafa Demung Besuki Situbondo) - Arifin, Samsul (Jurnal Manajemen Pendidikan Islam Darussalam, 2022)
The problems that befell the Indonesian people are getting more complex day by day than in previous times. Almost all aspects of life experience problems, such as aspects of religious life, education, politics, social law, culture, economy, and other aspects. The above is exacerbated by the degradation of the nation's moral values ??which is very concerning. Besides that, there are still frequent fights, riots, and brawls between students, and students which are very disturbing, and no less important is religious moderation which also still needs to be improved. This research is qualitative research, namely research that intends to understand the phenomenon of what is experienced by the research subject such as behavior, perception, motivation, and action. While the type of research used is field research. Field research is where the researcher goes directly to the field where the researcher will do it in order to obtain objective/accurate data and information in accordance with this discussion. The purpose of field research is to collect, process, and analyze data sourced from the research location. Thus, it can be found that behavior in mutual cooperation activities is a form of solidarity in these community groups. Gotong royong is a cultural feature of the Indonesian nation that applies from generation to generation so that it forms real social behavior in the values ??of social life.